Cardiovascular toxicity of tisagenlecleucel in children and adolescents: analysis of spontaneous reports submitted to FAERS - Wang, Ganggang; Su, Lin; Liu, Yanjun; Yang, Xiaohan; Li, Yi; Mei, Qi; Gao, Wen (Frontiers in Immunology, 2025)
BackgroundThe advent of tisagenlecleucel has been a major advance in the pharmacological treatment of relapsed/refractory B-cell acute lymphoblastic leukemia in children and adolescents. However, further research is required to better define its safety profile.ObjectivesTo determine the cardiovascular toxicity of tisagenlecleucel in children and adolescents.MethodsThe US Food and Drug Administration’s Adverse Event Reporting System was searched to identify cardiovascular adverse events (CVAEs) related to tisagenlecleucel in pediatric patients up to the age of 18 years.ResultsThe median time to onset of tisagenlecleucel-associated CVAEs was shorter than that of tisagenlecleucel-associated non-CVAEs (3 days [interquartile range (IQR) 1, 6] vs. 7 days [IQR 2, 54]). The median time to onset was longer in patients with fatal CVAEs than in those with non-fatal CVAEs (4 days [IQR 1, 12.5] vs. 2 days [IQR 1, 4]). The most frequently reported CVAEs were mitral valve disease, hypotension, and capillary leak syndrome. Patients who developed shock had the highest mortality rate (66.67%). Concomitant use of medication for a neurological disorder was an independent risk factor for CVAEs, and concomitant use of medication for a respiratory disease was an independent risk factor for fatal CVAEs. Most CVAEs were associated with cytokine release syndrome, and older patients had a more favorable prognosis.ConclusionsChildren and adolescents who receive tisagenlecleucel should be closely monitored for CVAEs, particularly during the first week of treatment.